Community Fodder Banks for addressing forage shortage in rainfed areas - Venugopalan, Visha Kumar; Prabhakar, M.; Gopinath, K. A.; Pankaj, P. K.; Rao, Ch. Srinivas (Indian Farming, 2016)
It is indeed a serious issue that forage production has not been picking up on a massive scale, in spite of significant progress in dairy development. As, simply increasing the area under fodder may not be a viable option, it calls out for developing strategies to bridge the huge gap. Taking into consideration the multi-faceted constraints faced by rainfed farmers, developing a community fodder bank would-be a viable option. However, considering the socio economic aspects this could be very challenging to institutionalize this concept at village level. The initial rapport with the farmers and making them understand the issue may be highly challenging. Identifying a common piece of land under common property resources may be another issue. Marginal and unproductive land needs to be identified and developed. Considering the limitations of traditionally cultivated fodder crops, selection of suitable fodder crops for growing on marginally unproductive farms and denuded community lands is still a researchable issue. As the supply of forage and feeds determine the profitability of animal husbandry and livestock being the major source of livelihood for the rural poor, we need to set our priority to address the needs of small farmers by developing various forage production systems, suitable for rainfed lands.